The relation between coronary artery disease severity and fragmented QRS complex in patients with left bundle branch block - Al-Daydamony, Mohamed M. (Egypt Heart J, 2017)
BACKGROUND: The diagnosis of coronary artery disease (CAD) in patients with LBBB represents a clinical challenge. The presence of fragmented QRS (fQRS) complex on surface ECG may be related to myocardial ischemia, scarring or fibrosis. OBJECTIVES: To investigate the relation between fQRS and the presence and severity of CAD in patients with LBBB. PATIENTS AND METHODS: 56 patients with symptoms suggesting CAD and complete LBBB were submitted to full history taking and clinical examination, complete 12-leads electrocardiography (ECG) to confirm the diagnosis of LBBB and to diagnose the fragmented wide QRS (f-wQRS) complex, echocardiography, and coronary angiography; lesions with ⩾70% narrowing in major epicardial artery or ⩾50% narrowing in the left main coronary artery were considered significant; and Gensini score was calculated. Patients were classified into two groups according to the presence or absence of f-wQRS. RESULTS: There were significantly more patients with obstructive CAD among patients with f-wQRS (p = 0.000053). Gensini score was significantly higher in patients with than in patients without fwQRS (p < 0.00001). f-wQRS was the only significant independent predictor of obstructive CAD. Sensitivity of f-wQRS in predicting obstructive CAD was 80.1%, specificity was 73.3%, positive predictive value was 72.4%, negative predictive value was 81.5%, and overall accuracy was 76.8%, p = 0.0022. CONCLUSION: Seeking for f-wQRS in patients with LBBB and suspected CAD is a simple, easy, available, method that may be helpful in noninvasive prediction of obstructive CAD.